A case of fibrodysplasia ossificans progressiva with sternocleidomastoid muscle calcification - Kumar, Kurrey Virendra; Rakesh, Nahrel (Indian Journal of Child Health, 2022)
Fibrodysplasia ossificans progressiva (FOP) is a rare and disabling genetic condition characterized by congenital skeletal malformations and progressive heterotopic ossification in humans with no ethnic, racial, gender, or geographic predilection. Diagnosis of this condition can be made clinically in the presence of radiographic evidence of heterotopic ossification along with symmetrical malformations of the great toes. The course of the disease is unpredictable and often progresses in the early childhood and patients become immobile and confined to a wheelchair by their twenties. Survival beyond the third decade is uncommon. We hereby report a case of FOP in a 7½-year-old girl.